Respuesta :
Answer:
Step-by-step explanation:
1) (x + 5)(x + 8)
=x(x +8)+5(x + 8)
=x^2+8x+5x+40
=x^2+13x+40
2)(x-1)(x+3)
=x(x+3)-1(x+3)
=x^2+3x-1x-3
=x^2+2x-3
3)(x-2)(x+9)
=x(x+9)-2(x+9)
=x^2+9x-2x-18
=x^2+7x-18
4)(2x+2)(x+9)
=2x(x+9)+2(x+9)
=2x^2+18x+2x+18
=2x^2+20x+18
5)(x-7)(3x+2)
=x(3x+3)-7(3x+2)
=3x^2+3x-21x-14
=3x^2-18x-14
NUMBER 1
(x + 5)(x + 8)
- factor the x
=x(x +8)+5(x + 8)
-Distribute
=x^2+8x+5x+40
-Combine like terms
=x^2+13x+40
-Final answer
NUMBER 2
(x-1)(x+3)
-Factor
=x(x+3)-1(x+3)
-Distribute
=x^2+3x-1x-3
-Combine like terms
=x^2+2x-3c
NUMBER 3
(x-2)(x+9)
-Factor
=x(x+9)-2(x+9)
-Distribute
=x^2+9x-2x-18
-Combine like terms
=x^2+7x-18
-Final answer.
NUMBER 4
(2x+2)(x+9)
-Factor
=2x(x+9)+2(x+9)
-Distribute
=2x^2+18x+2x+18
-Combine like terms
=2x^2+20x+18
-Final answer.
NUMBER 5
(x-7)(3x+2)
-Factor
=x(3x+3)-7(3x+2)
-Distribute
=3x^2+3x-21x-14
-Combine like terms
=3x^2-18x-14
-Final answer.